2021
DOI: 10.3390/jcm11010118
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Defects in Acute Myeloid Leukemia—Potential for Hemorrhagic Events

Abstract: Background and objectives: In acute myeloid leukemia (AML), extensive bleeding is one of the most frequent causes of death. Impaired activation and aggregation processes were identified in previous studies on platelet behaviour associated with this disease. This study’s aim was to examine platelet function in correlation with other haemorrhage risk factors (fever, sepsis, recent bleeding, uraemia, leucocytosis, haematocrit value, treatment). Design and methods: The analysis of platelet surface proteins (Glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The term platelet activation signaling and aggregation is also consistent with the previous literature that the platelet defects and other hemorrhagic symptoms are widely observed in AML patients [49]. The arachidonic acid metabolism is a process highlighted in a few cancer research publications, but the evidence for their involvement in AML is still accumulating [50,51].…”
Section: Aml Patient With Partial Gain and Partial Deletion Of Chromo...supporting
confidence: 86%
“…The term platelet activation signaling and aggregation is also consistent with the previous literature that the platelet defects and other hemorrhagic symptoms are widely observed in AML patients [49]. The arachidonic acid metabolism is a process highlighted in a few cancer research publications, but the evidence for their involvement in AML is still accumulating [50,51].…”
Section: Aml Patient With Partial Gain and Partial Deletion Of Chromo...supporting
confidence: 86%
“…Of note, besides low absolute platelet counts in AML patients, defects in activation and aggregation of the existing platelets may contribute to life-threatening hemorrhage. 8 Third, chemotherapy-related pericarditis was possible, albeit unlikely in our case. Previous literature reported hemorrhagic pericardial effusion in patients receiving either high-dose cytarabine (≥1,000 mg/m 2 /day) for more than 2 days or low-dose cytarabine (≤200 mg/m 2 /day) for more than 1 week.…”
Section: Discussionmentioning
confidence: 65%
“…On a platelet functional level, in a study comparing AML to immune thrombocytopenic purpura (ITP), flow cytometric measurements demonstrated morphologic platelet abnormalities indicative of an intrinsic dysfunction of platelet production and activity [ 63 ]. Moreover, this study and a more recent study comparing AML directly against healthy controls both found a significant reduction in the surface expression of platelet activation markers P-selectin and granulophysin, the platelet adhesion marker GP1b, and the platelet aggregation marker GPIIb-IIIa [ 63 , 64 ]. Such findings suggest potentially significant qualitative as well as quantitative platelet abnormalities contributing to elevated hemorrhage risk in APL and AML.…”
Section: Pathophysiology Of Hemorrhage In Aplmentioning
confidence: 88%